Strategic Management Analysis in Facing Business Competition - Wahyuni Nurindah Sulistiowati; Irmayani Misrah; Susiana (Jurnal Manajemen Bisnis, 2023)
In an organization, especially one that is engaged in the business sector, the most important thing is to have good strategic management. The respondents in this study were Holandia Stores, which are stores that serve wholesale and retail sales, with 15 employees, located on Jalan Safri Darwin, Wamena, Jayawijaya Regency. The purpose of this research is to find out the actions taken by Toko Hollandia in maintaining its business. This research is qualitative research with data collection techniques through interview observations and documentation. The form of goods traded in the form of raw food ingredients (Chicken, Fish, Shrimp, Meat, Frozen Food) and other household needs. Based on interviews conducted by respondents, the form of service provided by Toko Hollandia to retain old customers and attract new customers by providing services in the form of maintaining the quality of goods by paying attention to the expiration date of goods, especially for consumers who resell purchased goods is by giving discounts and provide free delivery service. The form of success described by Toko Hollandia is the increase in consumers who often shop at Toko Hollandia. In addition to serving consumers in Wamena, Jayawijaya Regency Toko Holandia also serves consumers outside the city of Wamena such as Puncak Jaya, and Lanny Jaya.